Operative Manual about WEB Switcher installation to be experimented at Antarctica Concordia Base Station - Palchetti, Enrico (Istituto di Fisica Applicata "Nello Carrara" - CNR, 2009)
The Concordia staff people had some problems with the Panasonic CF 30 Notebook Computer devoted to the acquisition of microwaves signals during the winter season 2009. This Notebook computer is inside the box radomex, on a tower, at 15 meter of hight from the Antarctic ice. In this season exit to check and restart the notebook personal computer Panasonic CF 30 could be extremely heavy and dangerous for the technical staff of Concordia Antarctic base. We are planning an alternative method to shutdown the Personal Notebook to avoid at the people to exit from Concordia base during the winter season. Object of this report is to describe the procedure of ONLINE web switcher installation and the procedure planned to restart the Notebook Personal computer from a severe problem.